KELEMBAGAAN USAHA MIKRO KECIL DAN MENENGAH DAN PEMBANGUNAN EKONOMI MASYARAKAT - Indra Suyahya (JABE (Journal of Applied Business and Economic), 2014)
Generally the number of entrepreneurs reached 3,75 million as per January 2012 or 1,56 percent of the total population of Indonesia. In 2010, there were still 0,24 percent while the Government is targetting the ratio of the number of entrepreneurs in Indonesia could reach 2,50 percent in 2013.Once problem to increase Small and Medium Enterprise is about the SME Institutional. By using descriptive methods and use the secondary data, research was designed to answer the following research problem:bureauctic system, capital problem, networking and ma rke tin g problem and also human resources capability to manage business unit . The result of study showed that there is a lo t of issues related to SME development and the cooperation on an SME institutional involving all related agencies needed to devel op s mall and medium enterprises and also give economic impact on the community reinforcement.